Trans-Normal distribution: A flexible model for duration and event-time data - YANG, Zhenlin (Institutional Knowledge at Singapore Management University, 2004)
A new family of distributions, called the trans-normal distribution is introduced. Its basic properties are presented. A closely related family of distributions called tran-t distribution is also given along with its basic properties. Trans-normal regression is used as an illustration on the usefullness of the new distribution.